Self-assembly of structurally persistent micelles is controlled by specific-ion effects and hydrophobic guests - Jäger, Christof; Hirsch, Andreas; Schade, Boris; Ludwig, Kai; Böttcher, Christoph; Clark, Timothy (Langmuir, 2010)
A combined study using cryo-TEM experiments and molecular dynamics simulations reveals remarkable details of the factors that affect the self-organization of specifically designed T-shaped amphiphilic dendrimers upon treatment of an aqueous solution with ultrasound under a layer of hexane. This treatment leads to dodecameric, structured micelles rather than the heptameric ones observed without hexane. Three-dimensional reconstruction of the cryo-TEM images provides very detailed structures of the micelles, and molecular dynamics simulations suggest that approximately 36 hexane molecules are needed to stabilize the dodecameric micelles. Sodium counterions are found to exert a significant stabilizing effect that results in an apparent attraction between the highly negatively charged polycarboxylate headgroups. DFT calculations support the observation that the formation of ion multiplets is especially crucial for this stabilizing counterion effect, which reduces headgroup repulsion. This and the increased hydrophobic stabilization that results from the hexane-enlarged core of the micelle lead to stable dodecameric micelles. The specific effects found for sodium counterions are largely absent for potassium. © 2009 American Chemical Society.